“O rio é uma riqueza imensa”: usos e tradições sobre a importância da água no sertão de Santa Quitéria-CE (1960-1980) - Mesquita, Maria Malena Paiva (2019)
When taking a tour of the backcountry these days, there is a possibility of finding a different space than many imagine. That wilderness as the deserted or backward space and which remains so, when understood in its reality and culture can give rise to the wilderness as a synonym for "progress." Regarding the structure of houses and the practicality that modernity and industrialization have brought to the backlands, we can list the use of running water, light, television and internet for a considerable number of homes.